2021
DOI: 10.1161/jaha.121.021824
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Circulatory Indexes Before and After Percutaneous Coronary Intervention in a Porcine Tandem Stenoses Model

Abstract: Background In tandem stenoses, nonhyperemic pressure ratio pullback is the preferred method to fractional flow reserve (FFR), based on the assumption of stable resting coronary flow. This study aimed to evaluate temporal changes of coronary circulatory indexes in tandem stenoses before and after angioplasty for proximal stenosis. Methods and Results Coronary tandem stenoses were created by porcine restenosis model with 2 bare metal stents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…First, coronary blood flow after PCI is sometimes unpredictable, which may affect the reliability of post-PCI NHPR values. 32 , 33 It is reported that the hemodynamic interdependence of NHPRs can be similar to that seen with FFR when the degree of serial coronary stenoses is very severe. 34 Second, this concept does not include the residual pressure gradient across the treated segment.…”
Section: Clinical Application Of Coronary Physiology In Special Condi...mentioning
confidence: 90%
“…First, coronary blood flow after PCI is sometimes unpredictable, which may affect the reliability of post-PCI NHPR values. 32 , 33 It is reported that the hemodynamic interdependence of NHPRs can be similar to that seen with FFR when the degree of serial coronary stenoses is very severe. 34 Second, this concept does not include the residual pressure gradient across the treated segment.…”
Section: Clinical Application Of Coronary Physiology In Special Condi...mentioning
confidence: 90%
“…Other explanations for these differences include suboptimal PCI results, measurement errors, and persistent hyperemia post-PCI, all of are challenging to control in clinical studies. 10,11…”
Section: Discussionmentioning
confidence: 99%
“…Other explanations for these differences include suboptimal PCI results, measurement errors, and persistent hyperemia post-PCI, all of are challenging to control in clinical studies. 10,11 One possible explanation for the presence of hemodynamic interdependence between serial coronary stenoses even at rest may be that there is a different mechanism for the regulation of resting coronary flow in serial coronary stenoses. The IDEAL (the Iberian-Dutch-English) study suggested an earlier impairment of microvascular autoregulation in serial coronary stenoses showing that resting flow velocity decreased gradually from a mild stenosis with FFR>0.91 to a more severe stenosis with FFR≤0.50, contradicting the conventional idea of constant resting coronary blood flow and directly supporting our findings.…”
Section: Discussionmentioning
confidence: 99%